Detection of bacillus cereus from imported rice in Malaysia - Tan, Pei Shze (Universiti Malaysia Sarawak (UNIMAS), 2015)
Bacillus cereus is frequently associated with foodborne illness outbreak. The common food vehicles for transmission of B. cereus are rice, rice products and starchy foods. Hence, it is crucial to investigate the biosafety of B. cereus in rice. The bacteria were enumerated by performing Most Probable Number (MPN) approach followed by Polymerase Chain Reaction (PCR) Assay targeting gyraseB (gyrB) gene at 475 bp. A total of 20 imported raw rice samples from various countries were evaluated. The finding indicated that the occurrence of B. cereus was >1100 MPN/g for all the imported raw rice samples. In addition, 100% of the imported raw rice samples were detected with presence of B. cereus. The result highlights the potential risk of B. cereus to cause food poisoning in rice. Hence, extra precautions in preparing, handling and storage of the rice are necessary to prevent microbial contamination.